The distribution of branchiobdellidan worms (Annelida: Clitellata) on the noble crayfish, Astacus astacus, in the Transcarpathian region, Ukraine - M. Shrestkha; S. Utevsky (Вісник Харківського Національного Університету Імені В.Н. Каразіна: Серія Біологія)
This study explores the distribution, abundance, and diversity of branchiobdellidans on freshwater crayfish in the Zakarpattia (Transcarpathian) region of Ukraine, focusing on populations in the Tereblya River and Lake Synevir. Surveys were conducted over the summer seasons of 2008, 2009, 2017, and 2022, examining a total of 68 noble crayfish (Astacus astacus Linnaeus, 1758). Four branchiobdellidan species were identified: Branchiobdella parasita (Braun, 1805), B. balcanica Moszynski, 1937, B. pentadonta Whitman, 1882, and B. hexadonta Gruber, 1883. This study presents the first records of B. hexadonta in Ukraine, expanding on the previously recorded presence of B. parasita and B. balcanica. Among the species observed, B. balcanica was the most prevalent, comprising 83% of the branchiobdellidans on individual crayfish in Lake Synevir and 64% in the Tereblya River. This species primarily occupied the claws, thoracic legs, and bases of the antennules, with cocoons mostly located in the lower cervical grooves. B. pentadonta was less frequent, accounting for 10% and 15% of branchiobdellidan specimens in Lake Synevir and the Tereblya River, respectively, and generally cohabited the same body regions as B. balcanica. B. hexadonta, detected exclusively in Lake Synevir, was found within the gill chambers and represented only 3% of the total branchiobdellidans. Visible damage to some gill filaments suggests that this species may exhibit parasitic behavior. B. parasita, known for its considerable size and widespread presence across native European crayfish populations, accounted for approximately 21% of the branchiobdellidan specimens. It was commonly found on the eyes, maxillipeds, and lateral sides of the cephalothorax. This species displayed protective behavior around its cocoons, actively moving to shield them. In comparison, the recently described B. bulgariensis, identified in Bulgaria, differs from B. parasita primarily in spermathecal structure and is associated with A. torrentium. In this study, our samples exhibited distinct spermathecal structures from both B. bulgariensis and B. parasita, indicating potential taxonomic variation that needs further investigation through molecular genetic analysis. In this study, we enhance the existing descriptions of branchiobdellidan species by providing detailed morphological and anatomical parameters. Our findings are based on both original species descriptions and our own research contributing to the understanding of the diversity and morphology of European branchiobdellidans.